2015
DOI: 10.1038/srep11045
|View full text |Cite
|
Sign up to set email alerts
|

Structural color printing based on plasmonic metasurfaces of perfect light absorption

Abstract: Subwavelength structural color filtering and printing technologies employing plasmonic nanostructures have recently been recognized as an important and beneficial complement to the traditional colorant-based pigmentation. However, the color saturation, brightness and incident angle tolerance of structural color printing need to be improved to meet the application requirement. Here we demonstrate a structural color printing method based on plasmonic metasurfaces of perfect light absorption to improve color perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
217
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(223 citation statements)
references
References 41 publications
0
217
5
1
Order By: Relevance
“…Recently, structural color systems based on engineered nanophotonic materials have emerged as an appealing alternative to absorptive dyes. [1][2][3][4][5][6][7][8][9][10][11][12] Among these examples are color filters based on plasmonics; filters which rely on the resonant interaction between incident photo ns and the free-electrons of nanoscale metal structures. Thus far, filters based on positive nanostructures, [4,7,9,[11][12][13][14][15] filters based on cavity apertures, [2,[16][17][18] and filters which combine both strategies [8] have been shown, each with distinct fabrication and geometrical solutions to achieving color "nanopixels" for selective white-light separation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, structural color systems based on engineered nanophotonic materials have emerged as an appealing alternative to absorptive dyes. [1][2][3][4][5][6][7][8][9][10][11][12] Among these examples are color filters based on plasmonics; filters which rely on the resonant interaction between incident photo ns and the free-electrons of nanoscale metal structures. Thus far, filters based on positive nanostructures, [4,7,9,[11][12][13][14][15] filters based on cavity apertures, [2,[16][17][18] and filters which combine both strategies [8] have been shown, each with distinct fabrication and geometrical solutions to achieving color "nanopixels" for selective white-light separation.…”
Section: Introductionmentioning
confidence: 99%
“…In that context, Yoon et al demonstrated a 1-D periodic amorphous Si thin-film grating structure that absorbs almost 90% of fully conical unpolarized light across the entire visible spectrum [1]. Cheng et al realized a 2-D periodic silver structure that exhibited nearly perfect absorption of incoherent light by plasmonic resonance in the visible spectral region [2]. Recently, techniques implementing absorption under coherent light interference have gained considerable attention due to several advantages including the use of linear optics and novel functionality not attainable by other means.…”
Section: Introductionmentioning
confidence: 98%
“…Although most of the devices presented here use a mixture of metal-dielectric multilayers so as to reduce the effects of the ohmic losses in metals [48][49][50], this costs extra time and money during fabrication [66][67][68][69]. So more recently all metal perfect absorbers [70] have been investigated.…”
Section: All Metal Subtractivementioning
confidence: 99%